Hemung and Sperrung Posttherapy ODGJ Verbal Language - Syafyahya, Leni; Yades, Efri (Environment-Behaviour Proceedings Journal, 2023)
The study aimed to describe the hemung, sperrung, and verbal language abilities of after therapy ODGJ. Methods through editing, coding, equivalent data analysis were used. Data obtained from YouTube Diman Khan TV. The results showed that hemung and sperrung occurred when asked about the deep conflict in the sufferer. The meaning of the ODGJ verbal language varies in communicating speech. There are coherent and incoherent. Coherent speech relates to other speeches, and incoherent speech is unrelated to following. After therapy,verbal language skills of ODGJ have developed.This development can be seen in reduction of hemung, sperrung, and incoherent sentences in communication.